Error features and their possible causes in simulated low‐level winds by WRF at a wind farm. (13th June 2013) - Wang, Chenghai; Jin, Shuanglong
ABSTRACT The WRF model is applied to simulate the low‐level wind field for a wind farm located in a typical arid region in northwest China for February 2008. The selected region has complex terrain with sparse vegetation. Overall, the WRF model reproduced the variation features of wind speeds and wind directions. However, the model overestimated the observed low‐level wind speeds, and there were large discrepancies for the low wind velocity (i.e. the errors of simulated winds increase with height and will be larger when the observed wind speeds are lower than 2.5 m/s). The features of the simulated errors and the possible causes in the model were analysed. The simulated low‐level wind in the afternoon is more accurate than that in early morning, which is usually unstable. Copyright © 2013 John Wiley & Sons, Ltd.